ANALISIS PERTANGGUNGJAWABAN PIDANA BAGI ANGGOTA KEPOLISIAN YANG TERLIBAT PEREDARAN NARKOTIKA - Valid, Wildan; Zuhdy, Mukhtar (LPPM Universitas Bina Bangsa, 2025)
Narcotics are substances or drugs that cause loss or alteration of consciousness, loss of sensation, reduce or eliminate pain, and can cause dependency. According to data from the National Narcotics Agency (BNN) in Indonesia, the number of narcotics users aged 15-64 years is approximately 4.8 million people. Within this context, there are cases where law enforcement officers, specifically police members, have abused their authority to consume and trade narcotics. This misconduct is exemplified by the narcotics trafficking case involving a high-ranking police officer, Inspector General TM, who violated Article 114 paragraph (2) of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics in conjunction with Article 55 Paragraph (1) item 1 of the Criminal Code. Another case was uncovered in the Pacitan Police Resort area involving First Inspector AW, with seized evidence of 571 grams of methamphetamine ready for distribution. This research aims to identify and analyze criminal liability and obstacles in implementing criminal accountability for police officers. This legal research uses normative juridical research and a statutory approach, by examining library materials from primary legal materials, secondary materials, and tertiary legal materials. Based on the research results, police members involved in narcotics cases can be held criminally liable as individuals under the law. The criminal liability of these police members is based on the principle of culpability, in accordance with Law Number 35 of 2009 concerning Narcotics. In addition to criminal penalties, police members found guilty can also be subject to internal disciplinary sanctions, including dishonorable discharge. In terms of implementing criminal liability, there are internal police obstacles, namely weak law enforcement mentality, lack of commitment and awareness, insufficient supervision and guidance, and psychological factors of law enforcement officers themselves.